2021
DOI: 10.3389/fendo.2021.783363
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia Is Associated With a Risk of Mortality in People With Type 2 Diabetes Mellitus

Abstract: BackgroundSarcopenia has reportedly been associated with increased risk of mortality in general populations. However, few studies have investigated the association between sarcopenia and mortality in older people with type 2 diabetes mellitus (T2D). This study aimed to investigate the effect of sarcopenia on incident all-cause mortality in older people with T2D.MethodsLow muscle strength were set at handgrip strength <28 kg for men and <18 kg for women, and low skeletal muscle mass index (SMI), e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 48 publications
0
28
1
Order By: Relevance
“…The elderly and those with comorbidities (immunocompromise, cardiopulmonary disease, cancer, diabetes, obesity, and kidney failure) are at heightened risk of experiencing rapid disease progression and mortality [ 3 ]. These comorbidities have in common chronic systemic inflammation, a higher prevalence of sarcopenia, loss of lean body mass, and protein-calorie malnutrition, which impairs immunity to infectious agents, such as SARS-CoV-2 [ 4 , 5 , 6 , 7 , 8 ]. The COVID-19 pandemic has heightened the risks of sarcopenia and protein-calorie malnutrition due to restrictions in physical activity from lockdowns, inaccessibility to exercise facilities, limited public transportation, and food insecurity from supply chain disruptions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The elderly and those with comorbidities (immunocompromise, cardiopulmonary disease, cancer, diabetes, obesity, and kidney failure) are at heightened risk of experiencing rapid disease progression and mortality [ 3 ]. These comorbidities have in common chronic systemic inflammation, a higher prevalence of sarcopenia, loss of lean body mass, and protein-calorie malnutrition, which impairs immunity to infectious agents, such as SARS-CoV-2 [ 4 , 5 , 6 , 7 , 8 ]. The COVID-19 pandemic has heightened the risks of sarcopenia and protein-calorie malnutrition due to restrictions in physical activity from lockdowns, inaccessibility to exercise facilities, limited public transportation, and food insecurity from supply chain disruptions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A correlation analysis was performed using Pearson’s correlation coefficient. We analyzed the correlation between body composition and dietary fiber intake in younger (age < 60 years) and older adults (age ≥ 60 years), separately ( 35 , 36 ). Moreover, we analyzed the correlation between body composition and soluble or insoluble dietary fiber intake, and the correlation between macronutrient intakes and body composition.…”
Section: Methodsmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) is one of the largest public health concerns leading to significant premature mortality and serious economic burden [ 1 , 2 , 3 , 4 ]. Evidence has shown that health-related fitness, such as cardiorespiratory fitness, muscle strength, and body composition, is an independent predictor of reduced quality of life, cardiovascular risks, and mortality among patients with T2DM [ 5 , 6 , 7 , 8 , 9 ]. Epidemiological studies found that patients with T2DM are frequently found to have low cardiorespiratory fitness and impaired muscle mass and strength as well as altered body composition [ 6 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%